Characteristics of Urgut Free Economic Zone Activity in Investment Processes in the Country - Djurayeva Iroda Bakhrom Kizi (Researchparks Publishing, 2023)
In this article, the directions and boundaries set by the leadership of the Republic of Uzbekistan within the framework of the organization and activity of the economic region